A CCCH zinc finger gene regulates doublesex alternative splicing and male development in Bombyx mori. (3rd November 2020) - Yang, Fangying; Zhang, Zhongjie; Hu, Bo; Yu, Ye; Tan, Anjiang
Abstract: Recent identification of a Piwi‐interacting RNA (piRNA)‐initiated sex determination cascade in the silkworm, Bombyx mori, provides novel insights into high diversity of insect sex determination pathways. In this system, the W‐chromosome‐derived Fem piRNA is the primary sex determination signal. A CCCH‐type zinc finger gene Masculinizer ( Masc ), which is targeted by Fem piRNA‐PIWI complex in female animals, is indispensable for male‐specific splicing of B. mori doublesex ( Bmdsx ). Although many genes involved in this cascade have been identified, the regulatory mechanisms of silkworm sex determination remain to be elucidated. Here we show that another CCCH‐type zinc finger gene, Bmznf‐2, is a masculinization factor in B. mori. Bmznf‐2 shows testis‐abundant expression and loss of Bmznf‐2 function via clustered regularly interspaced short palindromic repeats / single‐guide RNA‐mediated mutagenesis results in feminized differentiation and appearance of the female‐specific splicing variants of Bmdsx transcripts in males. In contrast, there is no phenotypic consequence in mutant females. In mutant males, relative messenger RNA expression levels of female‐dominant genes such as vitellogenin and sex‐specific storage protein 1 are significantly elevated while several male‐dominant genes are significantly down‐regulated. Furthermore, male mutants show delayed developmental timing, smaller body sizes of larvae and malformation of moth wings. Our data thus reveal that Bmznf‐2 plays an indispensable role in silkworm male sexual differentiation. Abstract : CRISPR/Cas9‐mediated Bmznf‐2 mutagenesis lead to delayed larval development and diminished body size in silkworm males. Bmznf‐2‐ deficient males produce female‐specific isoform of Bmdsx . Adult external genitalia characteristics of the male moths in Bmznf‐2 mutants develop a female‐specific genital papilla, degraded penis and defective clasper.